2008
DOI: 10.1186/1471-2296-9-12
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the work of general practitioners: a social science perspective on the context of medical decision making in primary care

Abstract: Background: The work of general practitioners (GPs) is increasingly being looked at from the perspective of the strategies and factors shaping it. This reflects the importance given to primary care services in health care system reform. However, the literature provides little insight into the medical decision-making processes in general practice. Our main objective was to better understand how organizational and environmental factors influence the work of GPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 38 publications
(32 reference statements)
2
25
0
4
Order By: Relevance
“…The method of GP remuneration and patient demands have been acknowledged as some of the main factors that influence the practice of GPs. 27 In Canada, both salary-based and fee-forservice GPs exist and it was found that there was an association between fee-for-service GPs and high rates of antibiotic prescribing. 28 It is postulated that this may affect the GP's decision to prescribe antibiotics during a consultation in Ireland.…”
mentioning
confidence: 99%
“…The method of GP remuneration and patient demands have been acknowledged as some of the main factors that influence the practice of GPs. 27 In Canada, both salary-based and fee-forservice GPs exist and it was found that there was an association between fee-for-service GPs and high rates of antibiotic prescribing. 28 It is postulated that this may affect the GP's decision to prescribe antibiotics during a consultation in Ireland.…”
mentioning
confidence: 99%
“…entretanto, não foi isso que verificamos. apenas três estudos utilizaram efetivamente teorias para analisar os resultados obtidos: Giddens' Structuration Theory (Geneau et al, 2008); Cognitive Continuum Theory (Randell et al, 2009) e Diffusion of Innovation Theory (BeaulIeu et al, 2008). Retomaremos esse ponto na discussão.…”
Section: Resultados E Análisesunclassified
“…em dois estudos canadenses, os pesquisadores se interessaram em analisar visões dos médicos sobre uma reforma da aPs (HunteR et al, 2004) e em investigar como os determinantes organizacionais influenciam o trabalho do médico e suas tomadas de decisão (Geneau et al, 2008). duas outras pesquisas abordaram o tema da satisfação dos profissionais com seu trabalho e sua relação com os modos de gestão (MaRtInFeRnandeZ et al, 2007;FReeBoRn;HooKeR;PoPe, 2002).…”
Section: A) Incorporação De Diretrizes E Conhecimentos Na Apsunclassified
See 1 more Smart Citation
“…Los tiempos de consulta en el primer caso varían entre 10 y 15 min mientras que en el segundo, lo hacen entre 20 y 45 min 13 . Finalmente, en la Argentina existe escasa bibliografía al respecto; sin embargo, es de destacar un estudio donde se pone de manifiesto la preocupación de los profesionales argentinos respecto de su calidad de vida en tanto actores del sistema de salud.…”
unclassified